(untitled) (Voice: A Biannual & Bilingual Journal, 2023)
The study was conducted in Nepalgunj Sub Metropolitan of Banke District. The objective of this study was to find out the problems faced by schools in sanitary practice such as water supply, toilet, waste dispose and school physical plant as well as role of headmaster and community people in sanitary practice of school. This descriptive type of research was based on primary data collected through questionnaire applying simple random sampling method. The population of the study were 505 (500 students and 5 headmaster) headmaster and students of Nepalgunj Sub Metropolitan. After collecting data it was checked, verified manually to reduce possible errors. The collected data were processed and placed in different table and analyzed in terms of percentage and frequency table. The status of sanitary practice of public school of Nepalgunj Sub Metropolitan were satisfactory but not well managed. They had no preplan or ideas regarding physical plant. The source of drinking water was satisfactory but 80 percent have financial problem to manage pure drinking water. The study reveals that 100 percent schools have toilet facility but lack of interest or facilities inside toilet is very poor and dirty. There is no any proper management of the waste disposal system in the school. Separate toilet for boys, girls and teacher is must. Pipe line drinking water is essential for permanent solution of the water in the school. To avoid this miserable condition, the government should strongly include regular program on sanitary facilities and its practice in the curriculum and school should apply the curriculum properly.